Examining the impact of the 3Cs: Content, collaboration and customisation of social media marketing on luxury fashion brand perception - Dr Richa Misra; Ekta Aggarwal; Dr Chhavi Taneja (The Retail and Marketing Review)
The rise of the internet and digitalisation, interconnected global markets, increasing income levels, and heightened consumer awareness about global luxury brands have largely propelled the demand for luxury goods. Social media has emerged as the predominant channel for generating awareness, persuasion, and purchase intent for luxury brands. There exists a notable gap and dearth of empirical evidence in the existing body of literature on the impact of Social Media Marketing (SMM) on customer’s loyalty and attachment to the brand. The purpose of this study is to investigate the impact of the 3 Cs of social Media Marketing (content, collaboration, and customisation) on the customers’ loyalty and attachment to luxury fashion brands, in turn impacting their willingness to pay for them. The study employed a structured questionnaire to gather data from 597 Gen Z customers who were actively engaged with luxury apparel brands; selected through convenience sampling. Partial least square-structural equation modelling (PLS-SEM) was used to analyse the conceptual model. The results indicated that while all the three Cs were found to be significant determinants of brand attachment and loyalty; content had the greatest impact, followed by collaboration and customisation. It was further observed that SMM had a more significant positive impact on brand attachment rather than brand loyalty. The study further revealed that brand loyalty had a greater impact on the customer’s willingness to pay a premium price, than brand attachment.